Dental Health Education: Chewing Gum Containing Xylitol in Junior High School Students - Tauchid, Siti Nurbayani; Nabila, Aulia; Purnama, Tedi (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: The high number of adolescent complaints related to dental and oral problems is related to the level of knowledge of adolescents in maintaining dental and oral health. Chewing xylitol gum is an alternative that has been proven to be quite effective in cleaning teeth from debris and plaque. Objective: This study aims to analyze the knowledge of students of junior high school PGRI 10 South Jakarta before and after being given education about chewing gum containing xylitol. Methods: This type of research is a quasi-experimental. The sample in this study amounted to 62 students, conducted in April 2022. Data collection by distributing pre-test and post-test questionnaires to measure knowledge before and after being given education about chewing gum containing xylitol. Data analysis using paired sample test. Results: Before the education was conducted, there were 9 students in the good knowledge category with a percentage of 14.5%, in the sufficient knowledge category there were 31 students with a 50.0% percentage, in the poor knowledge category there were 22 students with a 35.5% percentage. After education, there were 61 students in the good knowledge category with a percentage of 98.4%, in the sufficient knowledge category there was 1 student with a 1.6% percentage, in the poor knowledge category there were no students with a 0% percentage. The comparison of the average pre-test score is 6.05 while the total post-test average score is 9.40 with a p-value of 0.001. Conclusion: Education about chewing gum containing xylitol is effective in increasing the dental health knowledge of junior high school students.